2021
DOI: 10.1186/s40001-021-00559-x
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycosylation end products inhibit the proliferation of bone-marrow stromal cells through activating MAPK pathway

Abstract: Background The purpose of present study was to explore the mechanism of nuclear factor-kappa B (NF-κB), phosphatidylinositol 3-kinase (PI3K)/protein kinase B(PKB/Akt) and mitogen-activated protein kinase (MAPK) signaling pathways after intervention of advanced glycosylation end products (AGEs) on rat bone-marrow stromal cells (BMSCs). Methods Prepare and identify AGEs. BMSCs were isolated from 16 SD rats and cultured with different concentration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Moreover, treatment with MGF significantly inhibited the increase in microglial number in the hippocampus, suggesting that the neuroprotective role of MGF might be associated with its inhibitory effect on microglial activation. To further elucidate the potential targets of MGF, we performed bioinformatics analysis and found that MGF targets MAPK signaling, which regulates cell proliferation, stress response, inflammation, cell differentiation, and apoptosis (Li Z et al, 2021;Qin et al, 2021;Wang et al, 2021;Yang et al, 2021). More importantly, the MAPK signal pathway has been linked to several diseases, including depression (Duman et al, 2007;Wang and Mao, 2019;Humo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, treatment with MGF significantly inhibited the increase in microglial number in the hippocampus, suggesting that the neuroprotective role of MGF might be associated with its inhibitory effect on microglial activation. To further elucidate the potential targets of MGF, we performed bioinformatics analysis and found that MGF targets MAPK signaling, which regulates cell proliferation, stress response, inflammation, cell differentiation, and apoptosis (Li Z et al, 2021;Qin et al, 2021;Wang et al, 2021;Yang et al, 2021). More importantly, the MAPK signal pathway has been linked to several diseases, including depression (Duman et al, 2007;Wang and Mao, 2019;Humo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…High glucose environments can induce alterations in the expression levels of various signaling molecules, which impact the osteogenic differentiation of BMSCs through signal transduction, gene expression, as well as immune regulation. The most widely studied mechanisms that underlie HG-mediated BMSCs osteogenesis include ROS overproduction ( 97 , 98 ), AGEs-RAGEs signaling axis ( 99 ), and immunomodulation ( 100 , 101 ). etc.…”
Section: Impaired Bmscs Osteogenesis Under Hg Conditionsmentioning
confidence: 99%
“…Hyperglycemia is the most apparent clinical manifestation in diabetes mellitus, and excess free sugars in the body adversely affect many tissues and cells. High levels of extracellular free sugars have a direct inhibitory effect on the cellular activity of, both, osteoblasts and osteocytes ( 54 , 55 ). Osteoblasts exposed to high glucose levels exhibit reduced proliferation capacity, slow extracellular matrix synthesis, and subsequently slow maturation and mineralization.…”
Section: Pathogenesis Of Diabetic Bone Diseasementioning
confidence: 99%